2015
DOI: 10.1590/s1517-838246246220131102
|View full text |Cite
|
Sign up to set email alerts
|

Initial pH of medium affects organic acids production but do not affect phosphate solubilization

Abstract: The pH of the culture medium directly influences the growth of microorganisms and the chemical processes that they perform. The aim of this study was to assess the influence of the initial pH of the culture medium on the production of 11 low-molecular-weight organic acids and on the solubilization of calcium phosphate by bacteria in growth medium (NBRIP). The following strains isolated from cowpea nodules were studied: UFLA03-08 (Rhizobium tropici), UFLA03-09 (Acinetobacter sp.), UFLA03-10 (Paenibacillus kribb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
17
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
(42 reference statements)
5
17
0
1
Order By: Relevance
“…Gluconic acid was the most frequently produced (by 10 out of 11 strains) organic acid, similar to the findings of Chen et al 32 . www.nature.com/scientificreports www.nature.com/scientificreports/ Contrastingly, studies by Marra et al 33 and Surapat et al 19 reported propionic acid as the major organic acid, with the following order propionic> gluconic> tartaric> malic acid.…”
Section: Discussionmentioning
confidence: 85%
“…Gluconic acid was the most frequently produced (by 10 out of 11 strains) organic acid, similar to the findings of Chen et al 32 . www.nature.com/scientificreports www.nature.com/scientificreports/ Contrastingly, studies by Marra et al 33 and Surapat et al 19 reported propionic acid as the major organic acid, with the following order propionic> gluconic> tartaric> malic acid.…”
Section: Discussionmentioning
confidence: 85%
“…Positive P solubilization phenotypes were based on halo formation around bacterial colonies and results were expressed in the form of a Solubilization Index (SI), calculated as the halo diameter (d1) divided by the colony diameter (d2). The SI values can be used to classify the solubilization ability of a strain as low (SI < 2), intermediate (2 < SI < 4) and high (SI > 4) [ 115 ].…”
Section: Methodsmentioning
confidence: 99%
“…For assessment of phosphate solubilization at different initial pH (alkaline, neutral and acidic pH), three actinobacterial isolates were selected on the basis of Bonitur ranking. The three isolates, SA1, SA14 and S85 were quantitatively tested using colorimetric assay for their efficiency to solubilize phosphate at different initial pH of 6.0, 7.0 and 8.0 (Marra et al, 2015).…”
Section: Phosphate Solubilization Efficiency Of the Endophytic Actinomentioning
confidence: 99%